Mechanism of Concussion in Sports 2014
DOI: 10.1520/stp155220120160
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Impact Angle on the Dynamic Response of a Hybrid III Headform and Brain Tissue Deformation

Abstract: The objective of this study was to investigate the influence of impact angle on the dynamic response of a Hybrid III headform and brain tissue deformation by impacting the front and side of the headform using four angle conditions (0°, at the impact site and 5, 10 and 15° rightward rotations of the headform from 0°) as well as three additional angle conditions of -5, -10 and -15° (leftward rotations from 0°) at the side location to examine the effects of the neckform. The acceleration-time curves were used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Impact location is significant as impacts in the temporal region have been shown to be more likely to result in a concussion. 56,20…”
Section: Discussionmentioning
confidence: 99%
“…Impact location is significant as impacts in the temporal region have been shown to be more likely to result in a concussion. 56,20…”
Section: Discussionmentioning
confidence: 99%
“…These impact conditions are essentially the same angle but from different directions on the headform and the response will be governed by the geometry of the head and the geometry of the neck. Work conducted by Oeur 48 demonstrated that since the neck is asymmetrical, these two angle conditions can produce different results as a result of this neck construction. This observation is confirmed in these data, where impact locations 1–4 could be influenced by the asymmetry of the neck (Figure 10).…”
Section: Discussionmentioning
confidence: 99%
“…After determining the mechanical properties of the system components (Table 1), the motion constraints of the set were created. The hand moves along the shoulder using a linear spring with a stiffness of k. This design was used based on the experimental methods in previous studies (Oeur, 2012). After determining the desired model, a direct punch was applied to the lateral of the head in simulation conditions, because most of the blows to the head in martial arts are applied in the lateral direction of the head.…”
Section: Methodsmentioning
confidence: 99%